KODE DAN ALIH KODE SEBAGAI STRATEGI PENGAJARAN BAHASA INGGRIS - Umum B. Karyanto (JURNAL PENELITIAN, 2008)
This research is aimed to describe the form of code and code switching of certain code, whis is found in teaching and learning activities in class and the dominant factors that influence the form of code and code switching event. This research form is descriptive quatitative, with the case study taking location in MTs N (Model) Pemalang (State Junior High School for Islamic Studies of Model Pemalang). The significance of the research is to enable readers to know language use about a set of rules and characteristic of language variation in teaching and learning activities in classroom, in a multilingual society, especially at MTs N (Model) pemalang. Furthermore, the result of this research can be used as input to develop and contribute to teachers in developping skill of oral communication and teaching learning strategy effectiveness in MTs N (Model) environment.